Orthognathic surgery in the immunosuppressed post-organ transplant individual - Ian Jenkyn; Vijay Santhanam (Elsevier, 2021)
The use of immunosuppressive medication following organ transplant has become increasingly prevalent as both numbers of transplants being performed and long-term survival increase. As a result, there may be an increase in patients requiring oral and maxillofacial surgery, and in particular orthognathic surgery, whilst taking immunosuppressive medication. This report explores some of the considerations for orthognathic surgery in this cohort, and strategies to mitigate risks associated with surgical management.